Tradition of Public Society of Muara Bungo Jambi in Social and Economic Analysis - Widia, Umi (Proceedings International Conference on Education Innovation and Social Science, 2023)
The aims of this research are (1) to describe the implementation of the Punjungan Tradition in Karya Harapan Mukti Village, Muara Bungo Regency, Jambi Province; (2) To describe the Social Analysis of the implementation of the Punjungan Tradition in Karya Harapan Mukti Village, Muara Bungo Regency, Jambi Province; (3) To describe the Economic Analysis of the implementation of the Punjungan Tradition in Karya Harapan Mukti Village, Muara Bungo Regency, Jambi Province. The type of research used is a qualitative approach with ethnographic methods. This research was conducted in Karya Harapan Mukti Village, Kuamang Kuning 19, Pelepat Ilir District, Muara Bungo Regency, Province Jambi was carried out for about 3 months. Data collection techniques included interviews, observation, and documentation. The results show that the pavilion tradition of the people of Muara Bungo Jambi is a tradition that has been carried out for generations by the people of Muara Bungo Jambi. This tradition is carried out as a sign of invitation from the host who wants to hold a celebration party, be it a wedding, circumcision, or thanksgiving for the birth of a child. It can be concluded that the Punjungan Tradition creates a close bond of friendship between the people, it can be seen from the results showing that every time you get an adulation from someone, one day that person will be obliged to return or pay back that person. and also thanksgiving for the birth of a child.